A critical role for hemolysin in Vibrio fluvialis-induced IL-1β secretion mediated by the NLRP3 inflammasome in macrophages - Song, Liqiong; Huang, Yuanming; Zhao, Meng; Wang, Zhihao; Sun, Hui; Wang, Shujing; Kan, Biao; Meng, Guangxun; Liang, Weili; Ren, Zhihong (Frontiers in Microbiology, 2015)
V. fluvialis causes human diarrhea, but the pathogenesis is not well studied. We hypothesized that V. fluvialis-secreted hemolysin (VFH) may induce IL-1β secretion through the activation of the NLRP3 inflammasome and contribute to the pathogenicity of V. fluvialis. To examine this possibility, we constructed VFH mutant and complement strains and demonstrated that V. fluvialis-induced IL-1β production and cytotoxicity in human monocytic THP-1 cells and mouse macrophages is attributed to VFH. To evaluate the role of VFH in vivo, we infected adult C57BL/6 mice intraperitoneally and suckling C57/B6 mice orally with various strains. The mice treated with108 CFU wild-type V. fluvialis or cell-free supernatant containing VFH induced significantly higher IL-1β production in peritoneal lavage ﬂuid or in colon compared with those infected with the mutant strain, while no effect on TNF and IL-6 production was observed at day 5 or 24 h postinfection. VFH contributed to pathological changes and IL-1β release independent of colonization of V. fluvialis in the colon. VFH has no effect on the synthesis of pro-IL-1β, but rather it triggers the processing of pro-IL-1β into IL-1β. Furthermore, using deficient mouse strains, we verified that V. fluvialis-induced IL-1β is mediated through activation of caspase-1 and the NLRP3 inflammasome ex vivo. Confocal microscopy suggests that VFH contributes to cathepsin B release. Furthermore, V. fluvialis-induced IL-1β secretion requires potassium (K+) efflux and reactive oxygen species production. Our results provide new evidence for the role of VFH in the activation of the NLRP3 inflammasome and pathogenesis in response to V. fluvialis infection.